Implementasi Prinsip Good Governance dalam Meningkatkan Kualitas Pelayanan Publik di PT PLN (Persero) ULP Medan Kota - Qhataya, Chiya Laisa; Lubis, Yurial Arief (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
This study aims to analyze the implementation of the principles of good governance in improving the quality of public services at PT PLN (Persero) ULP Medan Kota, Medan Petisah District. The principles of good governance, which include transparency, accountability, community participation, effectiveness, efficiency, and law enforcement, are important factors in increasing customer satisfaction with PLN's services. The research method used is qualitative with a descriptive approach, where data is collected through in-depth interviews, observations, and documentation. Source triangulation techniques and methods are applied to ensure the validity of the data. The results of the study show that even though PLN ULP Medan Kota has implemented the principles of good governance, there are still several obstacles, such as lack of public understanding of the complaint mechanism, limited technological infrastructure, and slow response in handling customer complaints. To overcome these obstacles, PLN needs to increase service socialization, strengthen the digitalization system, and increase the capacity of human resources. With continuous improvement, it is hoped that the quality of PLN's services will increase, so that it can provide more transparent, accountable, and efficient electricity services for the community.